2017
DOI: 10.1371/journal.pone.0179462
|View full text |Cite
|
Sign up to set email alerts
|

A viral metagenomic approach on a non-metagenomic experiment: Mining next generation sequencing datasets from pig DNA identified several porcine parvoviruses for a retrospective evaluation of viral infections

Abstract: Shot-gun next generation sequencing (NGS) on whole DNA extracted from specimens collected from mammals often produces reads that are not mapped (i.e. unmapped reads) on the host reference genome and that are usually discarded as by-products of the experiments. In this study, we mined Ion Torrent reads obtained by sequencing DNA isolated from archived blood samples collected from 100 performance tested Italian Large White pigs. Two reduced representation libraries were prepared from two DNA pools constructed ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In pigs, several novel viruses are being constantly detected through metagenomic analysis like circovirus PCV3 , parvovirus (strain swine/ Zsana3/2013/HUN) (Hargitai et al, 2016), Parvovirus 7 (Palinski et al, 2016), etc. Porcine parvovirus 2 (PPV2), PPV4, PPV5, PPV6, and porcine bocavirus 1-H18 isolate (PBoV1-H18) (Bovo et al, 2017), first report for Ndumu virus in Uganda (Masembe et al, 2012), 2009 H1N1, pandemic influenza A virus (Greninger et al, 2010), Torque Teno virus, Porcine boca-like virus (Blomstrom et al, 2010), a new variant of Porcine astrovirus (Karlsson et al, 2015), all have been reported by metagenomics approach. Novel genotype of astrovirus 4 in nasal swab of pigs (Padmanabhan and Hause, 2016) has also been reported.…”
Section: Practical Aspects Of Viral Metagenomicsmentioning
confidence: 99%
“…In pigs, several novel viruses are being constantly detected through metagenomic analysis like circovirus PCV3 , parvovirus (strain swine/ Zsana3/2013/HUN) (Hargitai et al, 2016), Parvovirus 7 (Palinski et al, 2016), etc. Porcine parvovirus 2 (PPV2), PPV4, PPV5, PPV6, and porcine bocavirus 1-H18 isolate (PBoV1-H18) (Bovo et al, 2017), first report for Ndumu virus in Uganda (Masembe et al, 2012), 2009 H1N1, pandemic influenza A virus (Greninger et al, 2010), Torque Teno virus, Porcine boca-like virus (Blomstrom et al, 2010), a new variant of Porcine astrovirus (Karlsson et al, 2015), all have been reported by metagenomics approach. Novel genotype of astrovirus 4 in nasal swab of pigs (Padmanabhan and Hause, 2016) has also been reported.…”
Section: Practical Aspects Of Viral Metagenomicsmentioning
confidence: 99%
“…Recently Bovo et al (2017) demonstrated the potential of NGS dataset mining for viral metagenomics analysis in livestock.…”
Section: Role Of Ngs In Livestock Diseases and Other Complex Traitsmentioning
confidence: 99%
“…Breakthrough techniques in viral metagenomics and mining high throughput sequencing (HGS) datasets have highlighted the extraordinary diversity and persistence of parvoviruses and parvovirus-related sequences in an unexpected array of animals, including invertebrates [2,3,4]. These discoveries support the now generally accepted view that viruses are integral components of the microbiome and participate in the functioning of ecosystems of differing size and complexity, i.e., an individual organism or a population of organisms.…”
Section: Introductionmentioning
confidence: 98%